Cuentos y leyendas - Morales Yrigoin, Henry Alexander (2019)
The present work of professional sufficiency, entitled "Children's stories and legends", aims to support and argue through the application of a learning session to first-year high school students of the C.E.E. "Rafael Narváez Cadenillas"._x000D_ The adolescents of today have lost the great importance of knowing the folk tales of yesteryear and identifying with their culture, with their traditions, with ethnic diversity; and also know the formal structure of which it is composed. Against this, the need arises to inform students how this structure develops._x000D_ For this, a great diversity of learning strategies such as motivation, previous knowledge, cognitive conflict among others have been used. Which manage to arouse interest in students in order to be exploited by them._x000D_ The present work consists of three parts: in the first, the methodological strategies for the application of the learning session have been developed; in the second, we present the scientific argument with the help of supportive quotes and in the third, the psycho-pedagogical support.